Serum Vitamin D Level in Inflammatory Bowel Disease (IBD) and it’s Association with IBD Activity Abstract (Bangladesh Medical Journal, 2024)
Vitamin D influences innate immunity, which is believed to be the imbalance of it involved in the pathogenesis of Inflammatory Bowel Disease (IBD). Evidence exists on the association between vitamin D deficiency and inflammatory bowel disease (IBD). To assess the serum vitamin D concentration in patients with inflammatory bowel disease and to study the relationship of vitamin D level with disease activity in the patients with inflammatory bowel disease. This case-control study was carried out in the department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU) on 40 IBD cases, diagnosed on clinical background and 40 apparently healthy control group of similar age and sex. Blood samples were collected and serum vitamin D level was measured with Chemiluminescent Microparticle Immunoassay (CMIA) method in Biochemistry laboratory of BSMMU. The result were analyzed by SPSS version 22. Vitamin D deficiency and insufficiency were defined as serum concentration of ≤20 ng/ml and 21–29 ng/ml respectively. Disease activity were evaluated using the Harvey Bradshaw Index for Crohn’s Disease, Truelove and Witt’s Index for Ulcerative colitis. The vitamin D levels were correlated with disease activity in IBD patients comparing with control group. Mean (±SD) serum vitamin D levels were 16.27 ± 5.16 ng/ml in IBD group and 24.25 ± 6.69 in controls (p